A study of acceptance and hesitation factors towards tetanus, diphtheria, and acellular pertussis (Tdap) and influenza vaccines during pregnancy - Raquel Quiles; Mateus Deckers Leme; Denise Swei Lo; Alfredo Elias Gilio (Vaccine: X, 2023)
Introduction: Vaccination of pregnant women with tetanus, diphtheria, and acellular pertussis (Tdap) and influenza vaccines is desirable to reduce neonatal and maternal morbidity and mortality. However, vaccine coverage rates and acceptance are frequently below recommended rates. Objectives: To ascertain Tdap and influenza vaccine coverage rates in our population and to study the reasons behind sub-optimal rates. Method: A survey was submitted to pregnant or in their puerperium women at the University Hospital of São Paulo University. Data were obtained during two consecutive influenza seasons (2017–2018), and vaccination was verified through vaccination chart checking. Respondents were classified according to their status as “Received Tdap” and “Didn’t receive Tdap”, and as “Know” or “Doesn’t know” regarding their awareness of Tdap safety during pregnancy and protective effect on the newborn. Vaccine uptake and personal awareness of vaccination status were compared among these groups for Tdap and influenza vaccines. Results: In a studied sample of 207 patients (representative of the whole), coverage rates for Tdap and influenza vaccines were respectively 85.5% and 95.2%. Additionally, 84.5% received both vaccines. There was no vaccine refusal for Tdap and only 0.5% for influenza. For either Tdap or influenza vaccines, the main reason for not vaccinating was a lack of knowledge/information. Factors associated with not vaccinating Tdap during pregnancy were lower number of prenatal visits, being unemployed or freelance worker, not being aware of vaccine safety or its benefits for the baby, not being oriented by the doctor to be vaccinated, not being aware of personal vaccination status, and not having been vaccinated for influenza. Conclusion: While influenza vaccination coverage during pregnancy was ideal, Tdap rates were below recommended values. Significant factors associated with better coverage for Tdap during pregnancy included being employed and not being self-employed, (not yet reported in the Americas) and being aware of personal vaccination status.